La culture matérielle napoléonienne dans les expositions de l’après-Waterloo à Londres, 1815-1819 - Nicole Cochrane (Seminario di filologia francese, 2021)
This article examines exhibitions of Napoleonic art and material culture exhibited in London in the immediate years following the battle of Waterloo. Focusing on three main museums and exhibition spaces, George Palmer’s Waterloo Museum, William Bullock’s Egyptian Hall and the Waterloo Rooms in Pall Mall, it explores how display of Napoleonic art, furniture, clothing and weaponry to British audiences illuminates a tension in British public consciousness of Napoleon, the Napoleonic Wars and British cultural life. It demonstrates that museums were an important space for Napoleonic interaction, wherein exhibitions could simultaneously enforce narratives of defeat and British supremacy whilst also allowing for a tactile intimacy with objects of the ex-emperors personal and familial life.